Pelatihan Service Excellent pada Guru TK. Widyatama Sendangmulyo - Semarang - Rusmalia Dewi; Gusti Yuli Asih; Sri Kandariyah Nawangsih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this community service is to provide training on Service Excellence to Widyatama Kindergarten Teachers in order to improve their understanding of the challenges, skills and competencies needed to succeed in the service process. Customer service requires speed and awareness of comfortable and satisfying service in today's competitive era. Good service improves the school's reputation. This training will discuss how to improve teacher skills for reliable, comfortable and satisfying customer service. Initial observations showed that Widyatama Kindergarten Teachers provided mediocre service to students and parents due to limited circumstances. This made the owner of Widyatama Kindergarten concerned because of the lack of understanding of excellent service that could increase the number of students at Widyatama Kindergarten. The lack of knowledge about providing excellent service to students and parents made the team want to help find a solution about understanding excellent service to Widyatama Kindergarten teachers through Service Excellent Training. The process is to gather these teachers in the classroom and provide material on understanding and practicing Service Excellent in the form of lectures, stories and games as well as group discussions. The service team's hope for TK.Widyatama teachers is to be able to understand the results of the training, with an increased understanding of Service Excellent, it can improve the ability of these teachers to be even better in serving students and their parents, so that it can increase the number of students entering TK.Widyatama.